DUCTILE DAMAGE CHANGE ANALYSIS OF AXIAL SIMPLE DENTED PIPELINE IN CONSTRUCTION STAGE - WU Ying; WANG Le; XIE YanPing; TANG Na (Jixie qiangdu, 2019)
Mechanical damage can cause immediate or delayed failure of the pipe. The dent is the main form of mechanical damage. According to the Oyane ductile fracture criterion, the finite element method was used to simulate the axial simple dent caused by the construction stage. Analyzed the change of pipeline ductile damage degree in different pit sizes, pipe sizes and pipe pressures, the relationship between the dents depth and the ductile damage degree is obtained, which provides the theoretical basis for the safe design of the oil and gas pipelines with axial indentation during the construction stage.